The illness and death of Carrion - Monge, Carlos (1925)
The proof of the etiological Wart eruptive unit of Peru and La Oroya Fever call was made the day Carrión verrucous button inoculated and reproduced the malignant form of the disease (La Oroya fever), paying with his death their scientific devotion.